Genomic and Epidemiological Analysis of SARS-CoV-2 Viruses in Sri Lanka - Jeewandara, Chandima; Jayathilaka, Deshni; Ranasinghe, Diyanath; Hsu, Nienyun Sharon; Ariyaratne, Dinuka; Jayadas, Tibutius Thanesh; Panambara Arachchige, Deshan Madhusanka; Lindsey, Benjamin B.; Gomes, Laksiri; Parker, Matthew D.; Wijewickrama, Ananda; Karunaratne, Malika; et al. (Frontiers in Microbiology, 2021)
Background: In order to understand the molecular epidemiology of SARS-CoV-2 in Sri Lanka, since March 2020, we carried out genomic sequencing overlaid on available epidemiological data until April 2021. Methods: Whole genome sequencing was carried out on diagnostic sputum or nasopharyngeal swabs from 373 patients with COVID-19. Molecular clock phylogenetic analysis was undertaken to further explore dominant lineages. Results: The B.1.411 lineage was most prevalent, which was established in Sri Lanka and caused outbreaks throughout the country until March 2021. The estimated time of the most recent common ancestor of this lineage was 29th June 2020 (95% lower and upper bounds 23rd May to 30th July), suggesting cryptic transmission may have occurred, prior to a large epidemic starting in October 2020. Returning travellers were identified with infections caused by lineage B.1.258, as well as the more transmissible B.1.1.7 lineage, which has replaced B.1.411 to fuel the ongoing large outbreak in the country. Conclusions: The large outbreak that started in early October, is due to spread of a single virus lineage, B.1.411 until the end of March 2021, when B.1.1.7 emerged and became the dominant lineage.